THE CORRELATION BETWEEN STUDENTS’ RISK-TAKING AND VOCABULARY ACHIEVEMENT TOWARD SPEAKING SKILL OF THE SECOND GRADE STUDENTS OF MAN 2 KOTA MALANG - Widjajanti, Rina; Mariyo, Mariyo (Center of Language and Cultural Studies, 2022)
The objectives of this research are to find out the correlation between (1) vocabulary mastery and speaking skill (2) risk taking and speaking skill (3) vocabulary mastery and risk taking toward speaking skill. The research was carried out at MAN 2 KOTA MALANG. The research method was a quantitative correlation research. The population of the research is all the second grade students of MAN 2 KOTA MALANG in the academic year of 2019/2020. Consist of 180 students and it consist of six classes namely XI IPA 2, XI IPA 3, XI IPA 4, XI IPA 5, XI IPA 6 and XI IPA 7 The sample of the research consists of 30 students. The sampling used is a technique cluster random sampling. The techniques of collecting the data are: test for vocabulary mastery, questioner for risk taking and interview for speaking skill. The technique used to analyze the data was simple and multiple linear regression. The result of the study shows that there is a positive correlation between vocabulary mastery and speaking skill because the coefficient of correlation r-obtained is higher than r-table (0.679>0.361). There is a positive correlation between risk taking and speaking skill because the coefficient of correlation r-obtained is higher than r-table (0.735>0.361). There is a positive correlation between vocabulary mastery and risk taking toward speaking skill because the coefficient of correlation r-obtained is higher than r-table (0.791>0.361). From the the result of the research, it can be concluded that there is a positive correlation between vocabulary mastery and risk taking toward speaking skill. Therefore, vocabulary mastery and risk taking have contribution in increasing speaking skill.